Contamination of home-grown and retail vegetables with Clostridioidesdifficile. (April 2022) - Scholtzek, Anissa D.; Heise, Janine; Witt, Pascal; Hanuschik, Anna Maria; Maurischat, Sven
Abstract: The opportunistic intestinal pathogen Clostridioides difficile is the number one cause of nosocomial diarrhea in humans. In this study, C. difficile was isolated from 26.7% of potatoes and 1.9% of salads from German retail. The majority of strains possessed toxinogenic PCR-ribotypes that are associated with human clinical cases pointing towards a potential risk to human health. Highlights: High prevalence (26.7%) of C. difficile in home-grown and retail potatoes. Contamination rates in ready-to-eat mixed salads significantly higher than in whole salad. Most isolates (62.5%) belonged to toxigenic PCR-ribotypes (RT002, 005, 014, 023, 078). Association of identified PCR-ribotypes with human clinical cases. Most isolates (14/16) were susceptible to all six investigated antimicrobials.